Initial Market Assessment : Country Note--Vietnam - World Bank (2015)
Responding appropriately to the country’s high exposure and vulnerability to natural disasters, and capitalizing on a well-functioning insurance industry, Vietnam has embraced insurance mechanisms in disaster risk management and agriculture more vigorously than most developing countries. But some initiatives like the disaster risk reduction (DRR) strategy’s mandate to implement disaster risk insurance are yet to be conceived, while others such as the agriculture insurance scheme have been launched but experienced unsustainable outcomes and need strengthening. Technical assistance to guide this process can have substantial impact, and could include the consolidation of available risk modeling and hazard maps and closing major gaps these may have. Appropriate insurance of public assets will further strengthen the property insurance sector and justify investment in risk models and underwriting expertise that will subsequently be available for businesses and households. A public private partnership pursuing flood insurance for the urban poor in collaboration with existing community-based Disaster Risk Management programs could capitalize on the nascent micro-insurance market and further strengthen inclusive insurance. Vietnam has strong appetite for agriculture and catastrophe property insurance, and the governance structure as well as insurance industry to secure the desired impact of investments. Better incorporating agriculture and catastrophe property insurance principles in social safety net programs could increase the protection of larger populations.